Disappearing Hidden Treasures: The Carving of Wooden Sculptures of the Jah Hut Tribe - Abdullah Sani, Nor Edzrine; Abd Arif, Harleny (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Ukiran patung kayu merupakan satu simbol kekuatan dalam masyarakat suku kaum Jah Hut. Suku kaum Jah Hut menjadikan ukiran patung kayu ini sebagai bahan perantaraan bagi menjalankan upacara ritual dalam kehidupan mereka suatu ketika dahulu. Kajian ini dijalankan untuk mengetahui fungsi ukiran patung kayu dalam kehidupan masyarakat Orang Asli suku kaum Jah Hut di Kg Kol, Ulu Cheka Jerantut. Manakala, objektif kajian pula adalah untuk mengenal pasti sejauh mana penghasilan ukiran patung kayu dapat direalisasikan dalam kehidupan mereka sehingga ke hari ini. Pendekatan kualitatif melalui kajian kes telah digunakan bagi menerangkan secara deskriptif budaya masyarakat Orang Asli suku kaum Jah Hut. Temu bual tidak berstruktur, pemerhatian, analisis dokumen dan rakaman visual merupakan kaedah yang telah digunakan. Berdasarkan maklumat yang diperoleh semasa kerja di lapangan, dapatan kajian mendapati corak hidup suku kaum Jah Hut adalah berpegang kepada kepercayaan, adat dan warisan. Pada masa kini masyarakat Orang Asli telah mula mengecapi arus pemodenan dalam kehidupan mereka. Seiring dengan arus pemodenan, warisan tinggalan nenek moyang mereka seharusnya tidak dilupakan. Penulisan ini adalah bertujuan untuk berkongsi pengalaman dan pengetahuan pengkaji tentang khazanah yang semakin lenyap bagi seni ukiran patung kayu kaum Jah Hut Disappearing Hidden Treasures: The Carving of Wooden Sculptures of the Jah Hut Tribe Abstract: The wooden sculpture carving is a symbol of strength in the Jah Hut tribal society. The Jah Hut tribe used this wooden sculpture as an intermediate material to carry out ritual ceremonies in the past. This study was conducted to find out the function of wooden sculpture carving in the life of Orang Asli community of the Jah Hut tribe in Kg Kol, Ulu Cheka Jerantut. Meanwhile, the objective of the study is to identify how far the production of wooden sculptures can be realized in their lives to this day. A qualitative approach through case studies has been used to describe descriptively the culture of the Orang Asli community of the Jah Hut tribe. Unstructured interviews, observations, document analysis and visual recordings are the methods that have been used. Based on the information obtained during the work in the field, the findings of the study found that the lifestyle of the Jah Hut tribe is adhering to beliefs, customs and heritage. Nowadays, the Orang Asli community has begun to enjoy the current of modernization in their lives. Along with the currents of modernization, the legacy of their ancestors should not be forgotten. This writing aims to share the experience and knowledge of researchers about the disappearing treasures of the Jah Hut tribe wood sculpture art. Keywords: Culture, Jah Hut, Beliefs, Wood Sculpture.